Family Economics and Arrangement of the Family Patrimony by Santiago S Women (Chile), 1580-1650 [Economía Familiar y Gestión del Patrimonio Familiar por Las Mujeres Santiaguinas (Chile), 1580-1650] - Armijo-Reyes, A (Universidad Nacional de Colombia, 2016)
The present article examines the economic participation from the women of Chile s Santiago on the family and labor context, both as a wife and widow, in the period from 1580 to 1650. Analyzed the dowry documents from the young women, to identify the goods and capitals that got into the married life, thus providing, the economic foundation for the new family, in circumstances that the grooms declare don t had any goods that could favour the liability s marriage. Also, examined the testaments from the wives and widows, to analyze their participation like administrator of the goods and family means, in moments when they stayed alone, interfering thereby, on activities considered only for men, counteracting, the passive attitude and without mastery from the women of the colony.
Keywords: women; matrimonial dowry; patrimonial administration; Santiago de Chile